Exploring differences in communication behaviors between organic and conventional farmers - Fallys Masambuka-Kanchewa; Joy Rumble; Emily Buck (Journal of Agriculture, Food Systems, and Community Development, 2021)
This exploratory qualitative study sought to gain initial insights into how farmers involved in different production practices communicate with consumers. A thematic analysis of in-depth interviews conducted with eight organic and 12 conventional farmers in Ohio indicated that organic farmers are proactive in communicating with the public about their production practices, unlike conventional farmers, who focus on improving productivity. Furthermore, the organic farmers reported using different communication channels such as Facebook, flyers, and YouTube when communicating with consumers, while conventional farmers reported being busy working on their farms and not having time to communicate with consumers. Organic farmers’ involvement in communication activities with the public about their production practices and products was reported to stem from their beliefs and values toward sustainable farming practices and environmental conservation. Furthermore, unlike conventional farmers, most organic farmers sold their produce directly to consumers, and as such, used communication as a marketing tool. The active involvement of organic farmers in communicating with consumers may be attributable in part to increased media coverage about the benefits of organic farming practices. On the other hand, limited involvement of conventional farmers in communicating with the public may be partially attributable to limited media coverage about the benefits of conventional farming. Therefore, to ensure that consumers make informed decisions, there is a need to start developing standalone communication organizations and interventions committed to providing unbiased information about the benefits and disadvantages of the different farming practices.